The analysis of multidimensional poverty reduction effects of dual financial participation: evidence from rural household in China - Qianling Wang; Zhigang Chen; Li Gui (Humanities & Social Sciences Communications)
Abstract This study examines the impact of formal and informal financial participation on the multidimensional poverty status of rural households in China. Using panel data from the China Family Panel Studies (CFPS) covering the period 2014–2020, we construct a multidimensional poverty index based on the Alkire–Foster method and conduct empirical analyses employing panel Logit and dynamic Probit models. The results indicate that dual financial participation significantly reduces the likelihood of multidimensional poverty, a finding that remains robust after accounting for poverty state dependence and addressing endogeneity concerns. Further analysis reveals that formal financial participation primarily alleviates poverty in the dimensions of assets, risk resilience, and education, whereas informal financial participation is more strongly associated with improvements in living standards. The poverty reduction effects also exhibit substantial heterogeneity across households with different income levels, household head characteristics, and family structures. In addition, macro-institutional factors play a moderating role: higher agricultural insurance penetration and greater maturity of social credit systems enhance the poverty reduction effects of formal finance, while excessive financial regulation may undermine the effectiveness of informal finance. Overall, the findings provide comprehensive empirical evidence on the complementary roles of formal and informal financial systems in supporting rural poverty alleviation efforts in China.